Sinergia e resiliência entre a seca e a produção agrícola de sequeiro no semiárido do Ceará - Praxedes, Antonia Luana Fernandes (2021)
Periods of drought can bring significant negative impacts to the population, especially for family farmers in the semiarid region who cultivate rainfed food crops. The temporal and spatial climatic instability that characterizes the semiarid region also causes instabilities in the variables that define the production of these crops, such as: harvested areas, land productivity, and production value per hectare. Ceará is the Brazilian state that, proportionally, holds the largest area in the semiarid region, both from a technical point of view and from a point of view of official recognition by the Brazilian Government. In this state, which is very heterogeneous, the distribution of rainfall occurs in a very different way. So much so that the Ceará Meteorology and Water Resources Foundation (FUNCEME) divided the state into eight (8) sub-regions, fundamentally anchored in climatic differences. Among these regions, the most problematic, from this point of view, is Sertão Central and Inhamuns, which is composed of forty (40) municipalities, but this research worked with only twenty-nine (29) municipalities in this region, due to eleven municipalities that compose it have been recently emancipated and, therefore, did not have continuous series of variables in the period studied. This research aimed to answer the following questions: How is the synergy between the instabilities associated with rainfall and the variables defining the production of the main rainfed crops in the semiarid region of Ceará? Is there capacity for recovery or resilience of Ceará farmers who cultivate rainfed crops to the stresses caused by years of water scarcity? In order to answer these questions, this research worked with the following objectives: a) To classify rainfall in periods of scarcity, rainy and normality in the period from 1974 to 2019; b) Assess the associations between rainfall instabilities with those of variables that define the production of dryland bean, cassava and maize crops; and c) Assess the resilience of the production of these crops. Data on the production of beans, cassava and corn were collected from the Municipal Agricultural Surveys (PAM) of the IBGE between the years 1974 and 2019. Those referring to annual rainfall in the same period were sought from the Ceará Meteorology and Water Resources Foundation (FUNCEME) for the same period. The variables associated with agricultural production used in the research were: harvested area, land productivity; production value per hectare of crops. These variables were aggregated, and a factor analysis method was used with decomposition into main components to create a Synergy Index (INS), which measured the behavior of variables in dry periods vis a vis normality and rainy periods, which were accounted for in an aggregated way. Visual tests were performed through graphics and statistical proof of resilience using a dummy variable to test the hypothesis of the presence of resilience. The instabilities associated with the variables were estimated using the respective coefficients of variation (CV). The results showed that among the 29 municipalities studied, Iguatu had the lowest rainfall instability in the analyzed period, while Monsenhor Tabosa was the most unstable. Regarding the instability of the variables associated with crop production, it was verified that the harvested areas of cassava were the ones that presented the greatest instability in all studied regimes (drought, normal and rainy). The main conclusion of the research is that the production of beans, cassava and corn presents resilience when measured in an aggregated way by the INS. Regarding the variables studied, only areas harvested with cassava did not show resilience.